Parametric Modeling and Enhance the Creative Side in Interior Architecture Design - Hassan Ismail Ali , Osama (Dirasat: Human and Social Sciences, 2022)
Nature is an essential source of inspiration for designers with the variety of biological and complex organic forms it includes. Such a variation is difficult to capture with conventional design methods. Knowledge of advanced digital tools and parametric modeling, in particular, is crucial for finding a new way to solve design problems and help with creativity and innovation in design. The present research has stressed the importance of parametric modeling use in designing interior architecture, and fostering designers' innovation to come up with innovative and unconventional ideas and activities that satisfy all needs of the user. With parametric modeling methods, we can understand the nature of organic engineering, which will foster its analysis, measurement, and simulation in design thus helping designers to focus more on creativity and innovation. The research followed the descriptive, analytical, and applied methodology to shed light on the use of parametric modeling in designing interior architecture by some parametric modeling software. Furthermore, the research highlighted some of the outstanding global projects of parametric design. And highlighted some suggestions, Results, and recommendations that emphasize the role of parametric in enhancing Interior architecture.